Dynamic Changes in Microbial Composition During Necrotizing Soft-Tissue Infections in ICU Patients - Thy, Michael; Tanaka, Sébastien; Tran-Dinh, Alexy; Ribeiro, Lara; Lortat-Jacob, Brice; Donadio, Julia; Zappella, Nathalie; Ben-Rehouma, Mouna; Tashk, Parvine; Snauwaert, Aurelie; Atchade, Enora; Grall, Nathalie; et al. (Frontiers in Medicine, 2021)
Introduction Recent studies described the threat of emerging multidrug-resistant (MDR) bacteria in intensive care unit (ICU) patients, but few data are available for necrotizing skin and soft tissue infections (NSTI). In a cohort of ICU patients admitted for NSTI, we describe the dynamic changes of microbial population during repeated surgeries. Materials & methods This retrospective study compiled consecutive cases admitted for the management of severe NSTI. Clinical characteristics, NSTI features, morbidity and mortality data were collected. The microbiological characteristics of surgical samples obtained during initial surgery were compared with those obtained during the first reoperation, including persistence of initial pathogens and/or emergence of microorganisms. Risk factors for emergence of microorganisms and MDR bacteria were assessed by univariable and multivariable analyses. Results Among 100 patients (63% male, 58 years old [interquartile ratio (IQR) 50-68]) admitted for NSTI, 54 underwent reoperation with a median [IQR] delay of 3 [1-7] days. Decreased proportions of susceptible strains and emergence of Gram-negative bacteria, including Pseudomonas aeruginosa, staphylococci and enterococci strains, were reported based on the cultures of surgical specimen collected on reoperation. On reoperation, 22 (27%) of the isolated strains were MDR (p<0.0001 versus MDR bacteria cultured from the first samples). Broad-spectrum antibiotic therapy as first-line therapy was significantly associated with a decreased emergence of microorganisms. Adequate antibiotic therapy from the initial surgery did not modify the frequency of emergence of microorganisms (p=0.79) and MDR bacteria (p=1.0) or the one-year survival rate. Conclusion The emergence of microorganisms, including MDR bacteria, is frequently noted in NSTI without affecting mortality.